Students' learning outcomes and perceptions of the learning environments in physical chemistry laboratory classes in Thailand - Wititsiri, Sunan (Curtin University, 2007)
The purposes of this study were to analyse the learning environment, teacher-student interactions and educational outcomes in physical chemistry laboratory classrooms inThailand. In addition, the validation of the Chemistry Laboratory EnvironmentInventory (CLEI), the Questionnaire on Teacher Interaction (QTI) and Attitude Scale was examined. The sample was composed of 100 physical chemistry students in four Rajabhat Universities who responded to both Actual and Preferred Forms of the CLEI and QTI. Also, interviews and written stories were used with twelve students.Students' learning outcomes were investigated using a cognitive test, a practical test and the Attitude Scale. Before the questionnaires were used with the 100 students sample, the reliability and validity of the CLEI, QTI and Attitude Scale were confirmed with 198 tertiary science students in seven Rajabhat Universities. In addition, the results of students' interviews and written stories supported the validityof both the CLEI and QTI, and students improved their achievement outcomes. Thestudy found that there were differences between the students' preferred learningenvironments and what they perceived to be actually present. Associations were also found between students' perceptions of the classroom environment and student outcomes.